Theory of Aharonov-Bohm oscillations resulting from a charge density wave condensate flowing across an array of columnar defects in magnetic field - Rozhavsky, Alexander S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
We propose a microscopic theory for the Aharonov-Bohm oscillations, observed by Latyshev et al. in the magnetotransport experiment in NbSe3 with a charge density wave (CDW). CDW slides across an array of columnar defects in a high magnetic field. For the charge carrying quanta of CDW these defects are elementary solenoids carrying a magnetic flux. The quantum CDW current acquires a component oscillating with the flux, with the period hc/2e. Its magnitude is proportional to the concentration of columnar defects. The lower limit to the phase breaking length for these oscillations is set by the minimal Lee-Rice coherence length.